1980
DOI: 10.1111/j.1755-3768.1980.tb05742.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study in the Measurement of Corneal Endothelial Cell Density Using the Specular Microscope

Abstract: Six subjects who never wore contact lenses underwent six determinations of corneal cell density using each of two measurement modes: Mode A: the eye was applanted once and pairs of photographs were taken; Mode B: the eye was applanated and a single photograph was taken. For each measurement mode data were collected on two separate sessions (Test, Retest). Chi-square analysis revealed a significantly larger proportion of uncountable photographs from the first measurement session, and analysis of variance reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Several studies have identified and evaluated sources of measurement error (Sperling & Gunderson 1978;Azen et al 1980). In an investigation comparing central corneal endothelial cell density with peripheral cell density, no significant differences were found in central, superior, inferior and temporal densities in normal young adults, in normal older adults, in post-cataract adults, and in post-intraocular lens adults (Blackwell et al 1977).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have identified and evaluated sources of measurement error (Sperling & Gunderson 1978;Azen et al 1980). In an investigation comparing central corneal endothelial cell density with peripheral cell density, no significant differences were found in central, superior, inferior and temporal densities in normal young adults, in normal older adults, in post-cataract adults, and in post-intraocular lens adults (Blackwell et al 1977).…”
mentioning
confidence: 99%
“…Determination of endothelial cell density using the specular microscope has become increasingly valuable in the study of effects of various medications, chemicals or surgical procedures on the structure and function of the corneal endothelium (Binkhorst et al 1977;Hirst et al 1977). Several studies have identified and evaluated sources of measurement error (Sperling & Gunderson 1978;Azen et al 1980). In an investigation comparing central corneal endothelial cell density with peripheral cell density, no significant differences were found in central, superior, inferior and temporal densities in normal young adults, in normal older adults, in post-cataract adults, and in post-intraocular lens adults (Blackwell et al 1977).…”
mentioning
confidence: 99%